Draft genome and description of Corynebacterium haemomassiliense strain Marseille-Q3615T sp. nov., a new bacterium isolated from a 59-year-old man with chronic obstructive pulmonary disease symptoms. (November 2020) - Boxberger, M.; Antezack, A.; Magnien, S.; Cassir, N.; La Scola, B.
Abstract: In 2020, as part of a diagnosis attempt at IHU Méditerranée Infection in Marseille (France), a blood specimen was obtained from a 59-year-old man with chronic obstructive pulmonary disease symptoms, from which we isolated the new bacterial Corynebacterium haemomassiliense strain Marseille-Q3615 T . Matrix-assisted desorption ionization–time of flight mass spectrometry (MALDI-TOF MS) failed to identify this isolate. Analysis of the 16S ribosomal RNA gene and genome-to-Genome comparison suggested that this taxon belongs to a novel bacterial species within the family Corynebacteriaceae in the phylum Actinobacteria . We describe the main phenotypic characteristics, genome sequence and annotation of Corynebacterium haemomassiliense strain Marseille-Q3615 T, a new member of the Corynebacterium genus, which we propose as the type strain.